Impact of inquiry portfolios within a service-learning literacy field experience on preservice teachers' knowledge growth and GPA. (April 2023) - Eutsler, Lauren; Naik, Meena; Peecksen, Scott; Branton, Regina
Abstract: Debate remains around using portfolios to demonstrate knowledge growth. This mixed-method study examined 63 preservice teachers' knowledge to teach literacy, with a longitudinal measure of the impact on grade point average, using coarsened-exact matching with a sample of 522 college of education students. Regression results demonstrate achievement outpaced other matched students in the same college. Comprehensive portfolios containing artifacts and reflections demonstrate knowledge growth across these themes: a) Presentation: Experience review; b) Perspective taking: Empathetic observation; c) Understanding; d) Projections. Implications apply to teacher educators seeking to implement portfolios to assess student knowledge.